Partitioning of Organic Fertilizers in the Production of Kale - Alves, Thatiane Nepomuceno [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Nordi, Nicholas Taborda [UNESP]; de Oliveira, Marcelo Munhoz Venâncio; de Carvalho, Joseantonio Ribeiro [UNESP]; de Ávila, Jorgiani [UNESP]; da Silva, Gustavo Ferreira [UNESP]; Luís, Débora Cristina Mastroleo [UNESP] (FapUNIFESP (SciELO), 2025)
In the production of kale, nitrogen is one of the nutrients that the plant needs in greater quantity. Its application must be divided throughout the cycle, due to the loss by leaching. The objective of the research was to evaluate the effect of splitting organic fertilizers in topdressing on the production of kale. The experimental design was randomized blocks, with four replications, with seven treatments being evaluated in a 2 x 3 + 1 factorial scheme, the first factor was the fertilizers (castor bean cake and bokashi) and the second the application intervals (7; 14 and 21 days), in addition to the control without topdressing fertilization. The amount of each fertilizer was calculated to provide the same dose of N (40 kg ha-1) every 21 days. The following characteristics were evaluated: plant height (PH), stem diameter (SD), number of leaves per plant (NLP), leaf fresh matter mass (LFMM), leaf length at the beginning (LLB), middle (LLMe) and end (LLE) of the cycle and “SPAD” index. There was no interaction between the factors, for any characteristic evaluated. For all traits, the values observed in control was lower than treatments with topdressing. The increases of treatments of factorial in relation to the control were 37.8% (plant height); 31.8% (SD); 157.1% (NLP); 213.5% (MLFMM); 7.6% (LLB); 80.2% (LLMe) and 126.6% for the “SPAD” index. It is recommended to use castor bean cake and split it every 21 days as it results in less labor for application.
Keywords: bokashi; castor bean cake; nitrogen; organic agriculture